Embodied intelligent driving: concept, methods, the state of the art and beyond - SHEN Tianyu; LI Zhiwei; FAN Lili; ZHANG Tingzhen; TANG Dandan; ZHOU Meihua; LIU Huaping; WANG Kunfeng (智能科学与技术学报, 2024)
Embodied intelligence transcends the boundaries of traditional artificial intelligence by emphasizing the importance of interaction between machines and the physical world, facilitating the development of intelligent entities that combine hardware and software to learn from and adapt to their environments, thereby solving real-world problems. Inspired by this philosophy, the concept and framework of embodied intelligent driving are introduced, aiming at integrating the idea of embodied intelligence into the development and application of autonomous vehicles. Through the continuous interaction between physical agents, virtual agents, and real traffic scenes, intelligent driving systems can achieve precise perception, efficient execution, and autonomous evolution in complex scenes, enhancing the long-term adaptability of autonomous vehicles in open traffic environments. Based on the embodied intelligent driving framework, the relevant technologies are summarize and the development status and existing problems of such technologies are analyzed. Furthermore, thoughts and prospects in this field are demonstrated by exploring the important roles and application potential of virtual-real interactive data intelligence, foundation models and foundation intelligence, continuous learning and parallel intelligence. This paper is expected to promote innovative research and the application on embodied intelligent driving in a wider range of scenarios, and provide new ideas and solutions for the development of mobile robot systems such as intelligent vehicles.